2022
DOI: 10.3390/biomedicines10112687
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Optimization of Gene Electrotransfer Protocol Using Hard-to-Transfect UT-7 Cell Line as a Model

Abstract: Non-adherent cells are difficult to transfect with chemical-mediated delivery methods. Electroporation is an attractive strategy to transfer the molecules of interest into suspension cells. Care must be taken with the viability of the transfected cells since parameters, which increase cell membrane permeability, subsequently increase transfection efficiency, leading to higher cell death indices. We intended to evaluate the distribution of hard-to-transfect UT-7 cells among different subpopulations: transfected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Gene electrotransfer is a nonviral method for gene transfer into cells and tissues that exploits short high voltage electric pulses. The interest in this method's applicability increased with time after proving GET efficacy, especially on nonadherent hard-to-transfect cells and tissues [10,12,15,25,34]. Most of the gene electrotransfer protocols utilize long pulses that are in the millisecond range (2-20 ms) [17,35]; differently, ESOPE protocol exploits short 100 µs pulses for electrochemotherapy to boost the uptake of chemotherapeutic medications [32,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene electrotransfer is a nonviral method for gene transfer into cells and tissues that exploits short high voltage electric pulses. The interest in this method's applicability increased with time after proving GET efficacy, especially on nonadherent hard-to-transfect cells and tissues [10,12,15,25,34]. Most of the gene electrotransfer protocols utilize long pulses that are in the millisecond range (2-20 ms) [17,35]; differently, ESOPE protocol exploits short 100 µs pulses for electrochemotherapy to boost the uptake of chemotherapeutic medications [32,36].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have attempted to improve the efficiency of gene electrotransfer by modifying electric field settings, pulsing buffers, plasmid concentrations, and the shape and material of the electrodes [21][22][23]. However, optimization of the electric field parameters and plasmid concentration has been found to be the most effective for improving gene electrotransfer efficiency [24,25]. Studies have demonstrated that factors such as the duration of the squarewave pulse, the quantity of pulses, the strength of the field, and the frequency of pulse application can collectively impact gene delivery through electroporation [26][27][28].…”
Section: Introductionmentioning
confidence: 99%